Efforts to Increase Employee Work Motivation at the Office of the Mayor of Medan Economic Section - Muhammad Habrul Aji; Andri Soemitra (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
Motivation is a process which encourages someone to do their work in order to fulfill the goals they set and if those goals are met then the person will feel satisfied with what they are doing. The purpose of this study was to see what efforts were made to increase employee motivation at the Medan mayor's office, especially in the economy. The research methodology carried out is by using qualitative methods. The results show that the program to increase employee work motivation at the Medan Mayor's Office has one component, namely the occupational safety and health program.